Patient satisfaction with nurses' care is positively related to the nurse–patient relationship in Chinese hospitals: A multicentre study - Guo, Shujie; Chang, Yulan; Chang, Hongwei; He, Xiaoxiao; Zhang, Qiuxue; Song, Baoyun; Liu, Yilan (Frontiers in Public Health, 2023)
Objective：This study aims to explore the correlation between the nurse–patient relationship and patients’ satisfaction with nursing care to form a basis for corresponding intervention measures. Method: A total of 29,108 patients from 107 hospitals in 30 provinces/municipalities in China were investigated using a general information questionnaire, the Nursing Care Satisfaction Scale and Relational Care Scale. Results: The average score of the nurse–patient relational care scale was 4.38 ± 0.57, and the average score of patients’ satisfaction with the nursing care scale was 5.40 ± 0.86. There were statistically significant differences in the total average score of nursing care satisfaction among patients of a different age, gender, marriage, children’s status, education level, occupation, residence, family per capita monthly income, type of medical insurance, medical department and regional patient characteristics (P < 0.05). The correlation analysis showed that nurse–patient relational care and each dimension score were positively correlated with the nursing care satisfaction score (P < 0.001). The results of the multiple linear regression analysis showed that patients’ age, marriage, region, department, income, type of medical insurance and caring, trust and professional ethics dimensions of relational care were the influencing factors of nursing care satisfaction (P < 0.05). Conclusion: The construction of nurse–patient relational care improves nursing care satisfaction, reduces nurse–patient disputes, promotes the early rehabilitation of patients and ensures patient safety.